Ethnochemistry-Based E-Module: Does it Effect on Improving Students' Chemical Literacy - Citra Ayu Dewi; Yahdi Yahdi; Aulia Sanova (Yayasan Keluarga Guru Mandiri, 2024)
The low chemical literacy of students is caused by the lack of involvement of the socio-cultural environment in chemistry learning. Ethnochemistry is an exciting learning approach today because it can catalyze chemical literacy in chemistry education in the twenty-first century. This study aims to analyze the effectiveness of ethnochemistry using e-modules in improving students' chemical literacy competency. The research method used is quasi-experimental. The research subject is the chemistry education study program at two universities in West Nusa Tenggara. The sampling technique uses cluster random sampling to select the research sample. The sample consisted of two classes, namely class IIA (totaling 100 students), which served as the experimental group, and class IIB (which also consisted of 100 students), which served as the control group. Data collection was carried out using a chemical literacy essay test. Statistical tests, including the ANOVA and N-Gain, were used to evaluate students' chemical literacy. The results showed that 1) ethnochemistry-based e-modules have a significant effect on chemical literacy; 2) The use of e-modules in ethnochemistry can improve students' chemical literacy, especially in solving environmental problems. Thus, this research contributes to integrating E-module content with hybrid-based ethnochemistry as a 21st-century learning innovation. The implication of this study is that students' chemical literacy can be improved through ethnochemistry-based e-modules.